Scandal and reputation at the court of Catherine de Medici - McIlvenna, Una (Women and gender in the early modern world, 2016)
Introduction: Catherine de Medici and the myth of the "flying squadron" -- Court life and its critics: the rise in satirical literature -- The dissemination of scandal: news culture in early modern France -- Venomous rumours: the scandal of Isabelle de Limeuil -- Word of honour: Françoise de Rohan versus the Duke of Nemours -- The triumph of the matriarch: Anne d'Este, Duchess of Guise, Duchess of Nemours -- Conclusion: a re-assessment of scandal